How does the pattern of root metabolites regulating beneficial microorganisms change with different grazing pressures? - Yuan, Ting; Ren, Weibo; Wang, Zhaoming; Fry, Ellen L.; Tang, Shiming; Yin, Jingjing; Zhang, Jiatao; Jia, Zhenyu (Frontiers in Plant Science, 2023)
Grazing disturbance can change the structure of plant rhizosphere microbial community, and feedback on plants to promote plant growth or enhance the plant's defenses. However, how these change happened and varied with different grazing pressures? what role does the root metabolites play on this key process? We still know little about these questions. Here, we investigated the effects of different grazing pressures on the microbial community composition and explored via metabolomics the driver through which different grazing pressures changes the rhizosphere microbiome. The results indicated that grazing changes microbial community composition, function and co-expression network. Under light grazing (LG), some saprophytic fungi such as Lentinus sp., Ramichloridium sp., Ascobolus sp., Lentinus sp. and Hyphodermaand sp. were significantly enriched whereas potential beneficial rhizobacteria, such as Stenotrophomonas sp., Microbacterium sp., and Lysobacter sp. were significantly enriched in heavy grazing (HG). And beneficial mycorrhizal fungi Schizothecium sp. were significantly enriched both in LG and HG treatment. Moreover, all these enriched beneficial microorganisms were positively correlated with root metabolites as amino acids (AAs), organic acids (SCOAs) and alkaloid. Our results demonstrated plant root metabolites especially amino acids (L-Histidine), may recruit specific saprophytic fungi to promote litter decomposition, fecal decomposition, and the absorption of soil mineral nutrients in LG treatment, so as to participate in the energy cycle of grassland ecosystem to promote plant growth. However, under HG treatment, the plants can recruit plant growth-promoting rhizobacteria and beneficial mycorrhizal fungi by AAs (N-Acetyl-L-Aspartic Acid, L-Tryptophan, L-Asparagine and L-Ornithine), SCOAs (3-Ureidopropionic Acid) and alkaloid (Diethanolamine, 3-Indoleacrylic acid and 6-Deoxyfagomine) to help alleviate the heavy grazing stress and improve the plant's defenses. In summary, our findings suggest that the grassland plant can recruit beneficial microorganisms by manipulating their root metabolites and the response strategies varied with different grazing pressures in typical grassland ecosystems.